2018
DOI: 10.22159/ajpcr.2018.v11i4.23849
|View full text |Cite
|
Sign up to set email alerts
|

Design, Formulation, and Characterization of Stearic Acid-Based Solid Lipid Nanoparticles of Candesartan Cilexetil to Augment Its Oral Bioavailability

Abstract: Objective: Poor aqueous solubility and suboptimal oral bioavailability hamper the therapeutic efficacy of candesartan cilexetil (CDC). This study is designed to prepare solid lipid nanoparticle (SLN) of CDC and to enhance the oral absorption of CDC compared with free drug suspension.Methods: The development and characterization of CDC-loaded SLN, using stearic acid as main encapsulating lipid, stabilized with poloxamer188 using “modified emulsification-ultrasonication technique.”Results: CDC-SLN with a total d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
1
21
0
2
Order By: Relevance
“…fig. (8) and (9) show the DSC results for dispersions prepared with aerosil ® 200 and sylysia ® It is obvious from ( fig. (8) that solid dispersions prepared with aerosil 350, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…fig. (8) and (9) show the DSC results for dispersions prepared with aerosil ® 200 and sylysia ® It is obvious from ( fig. (8) that solid dispersions prepared with aerosil 350, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…According to the classical Noyes-Whitney equation, this will increase the dissolution rate [3] One way to increase the surface area to improve the dissolution rate is by reducing the particle size using micronization. Alternatively, the dissolution rate of (CAN) can be improved also by increasing its aqueous solubility through formation of a cyclodextrin inclusion complex [4] or through the preparation of self-micro emulsifying drug delivery systems (SMEDDS) [5][6][7] or by developing (CAN)-loaded solid lipid nanoparticles (CLNs) [8,9] or through formation of solid dispersion involving effective P-gp inhibition (P-glycoprotein-which is an efflux pump distributed throughout the body especially in the , and is responsible for limiting cellular uptake and the distribution of xenobiotics by pumping any them back into the intestinal lumenfor optimal drug delivery [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…So, the combined effect of both electrostatic and steric stabilization is expected in the SLN formulations 72 . In previous studies, it was found that due to the carboxyl group of stearic acid the formulation which contains stearic acid as the lipid phase has shown negative values of zeta potential 67 .…”
Section: Fig 1: Types Of Nanocarriermentioning
confidence: 99%
“…The dissolution rates for the prepared microsponges formulae were carried out using USP paddle method at 50 rpm in 900 ml of phosphate buffer H 6.8 containing 0.35% w/v Tween 20 as a dissolution media, maintained at 37±0.5°C. The samples were collected at specified time intervals (5,10,15,20,25, and 30 min), filtered through Whatmann filter paper and assayed spectrophotometrically at 254 nm. An equal volume of fresh medium, which was pre-warmed at 37°C, was replaced into the dissolution media after each sampling to maintain a constant volume throughout the test [13,14].…”
Section: In Vitro Dissolution Studymentioning
confidence: 99%
“…CC is a highly lipophilic compound. Therefore, it is necessary to find a new approach to enhance the oral bioavailability of the drug [5].…”
Section: Introductionmentioning
confidence: 99%